2014
DOI: 10.1016/j.procs.2014.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on Analyzing EEG Alpha Brainwave Signal Activities Based on Visual Stimulation

Abstract: A current conceptual studies and researches are focusing on rehabilitation of SCI (Spinal Cord Injury) and stroke sufferer by using FES (Functional Electrical Stimulation) induced. The amount of FES induced is depending on level of injury and the muscle since the electrical stimulate is only in μvolt. To have sufficient amount of FES stimulation, the brain signal that transmit to muscle movement is the main controller of the body. Therefore, this study is conducted to measure brainwave signal of alpha wave ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…The condition of relaxation when listening to the Quran is demonstrated by a description of the activity of the brain, which is dominated by the α wave (Isa et al, 2014). It was also found that the state of relaxation reached while listening to murattal helps with anxiety.…”
Section: Introductionmentioning
confidence: 93%
“…The condition of relaxation when listening to the Quran is demonstrated by a description of the activity of the brain, which is dominated by the α wave (Isa et al, 2014). It was also found that the state of relaxation reached while listening to murattal helps with anxiety.…”
Section: Introductionmentioning
confidence: 93%
“…Blocks. Mittlerweile wurde empirisch abgesichert, dass sich eine verstärkte neuronale α-Wellen-Aktivität durch visuelle Stimuli provozieren lässt [20] und dass damit neurovegetative Entspannung korreliert [4] [30].…”
Section: Biodiversität Und Neurobiologieunclassified
“…The frequency components are often grouped into bands, these are the alpha, beta, gamma, delta and theta bands. The frequency limits of the bands are not precisely defined, the limits used are slightly different for different articles [5,7,11]. Ranges used by us are summarized in Table 1.…”
Section: Data Preprocessingmentioning
confidence: 99%